The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.jmb.2004.06.044
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Unusual Palindromic Transmembrane Helical Hairpin Formed by SARS Coronavirus E Protein

Abstract: The agent responsible for the recent severe acute respiratory syndrome (SARS) outbreak is a previously unidentified coronavirus. While there is a wealth of epidemiological studies, little if any molecular characterization of SARS coronavirus (SCoV) proteins has been carried out. Here we describe the molecular characterization of SCoV E protein, a critical component of the virus responsible for virion envelope morphogenesis. We conclusively show that SCoV E protein contains an unusually short, palindromic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(146 citation statements)
references
References 32 publications
(40 reference statements)
8
134
3
1
Order By: Relevance
“…67,68 Dichroic ratios were determined as described previously. 69 The dichroic ratios for amides I and A were calculated from the spectra in H 2 O and D 2 O, respectively.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…67,68 Dichroic ratios were determined as described previously. 69 The dichroic ratios for amides I and A were calculated from the spectra in H 2 O and D 2 O, respectively.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…[17] To detect a single iodine label via difference analysis of the electron density curves of labeled and unlabeled peptides, very high peptide-to-lipid ratios are often required-in the range of P/L % 1/10. [13,16] The necessity for an iodine label improvement has been recognized at least for two reasons. First, there are many transmembrane peptides, especially those connected to an inner and outer membrane domain, that are not at all or only hardly reconstitutable within the membrane environment at such high P/L ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Small envelope (E) proteins are structurally conserved within different coronavirus groups, yet exhibit little sequence similarity among these groups [1,73]. In general, coronavirus E proteins are small proteins (varying in size from 76 to 109 amino acids), with an unusually long hydrophobic stretch (25-30 residues) located in between hydrophilic N and C terminus (~8 and ~ 40 residues respectively).…”
Section: Small Envelope (E) Proteinmentioning
confidence: 99%
“…The unusual length of the hydrophobic segment of SARS-CoV E protein has posed a problem with respect to assigning the topology to the protein. Arbely et al [73] presented a detailed structural model for SARS-CoV E protein, which determined the topology of the protein and the effects upon the lipid bilayer thereof. The results showed that SARS-CoV E protein contains an unusually short palindromic transmembrane helical hairpin around a previously unidentified pseudo-center of symmetry, a structural feature that seems to be unique to SARS-CoV.…”
Section: Small Envelope (E) Proteinmentioning
confidence: 99%